Updated Studies on the Development of HIV Therapeutic Vaccine - Larijani, Mona S.; Ramezani, Amitis; Sadat, Seyed Mehdi (Current HIV Research, 2019)
Background: Among the various types of pharmaceuticals, vaccines have a special place. However, in the case of HIV, nearly after 40 years of its discovery, an effective vaccine still is not available. The reason lies in several facts mainly the variability and smartness of HIV as well as the complexity of the interaction between HIV and immune responses. A robust, effective, and longterm immunity is undoubtedly what a successful preventive vaccine should induce in order to prevent the infection of HIV. Failure of human trials to this end has led to the idea of developing therapeutic vaccines with the purpose of curing already infected patients by boosting their immune responses against the virus. Nevertheless, the exceptional ability of the virus to escape the immune system based on the genetically diverse envelope and variable protein products have made it difficult to achieve an efficient therapeutic vaccine. Objective: We aimed at studying and comparing different approaches to HIV therapeutic vaccines. Methods: In this review, we summarized the human trials undergoing on HIV therapeutic vaccination which are registered in the U.S. clinical trial database (clinicaltrials.gov). These attempts are divided into different tables, according to the type of formulation and application in order to classify and compare their results. Result/Conclusion: Among several methods applied in studied clinical trials which are mainly divided into DNA, Protein, Peptide, Viral vectors, and Dendritic cell-based vaccines, protein vaccine strategy is based on Tat protein-induced anti-Tat Abs in 79% HIV patients. However, the studies need to be continued to achieve a durable efficient immune response against HIV-1.
Keywords: vaccine